Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah Yang Dimoderasi Lingkungan Eksternal - Yuliana Anggreani Dua Delang Kolit; Wahidahwati Wahidahwati; Titik Mildawati (Politeknik Ganesha Medan, 2023)
This study aimed to examine and analyze the effect of the accounting information system and human resources on the quality of and human resources on the quality of local government financial statements, which were moderated by the external environment. The method used in this study was quantitative research, the data collection technique used purposive sampling with the slovin formula. In line with that, there were 56 employes as the sample. The data were primary with questionnaires survey as the instrument of data sampling to thr respondents the data analyze technique used multiple linear regression and Moderated Regresaion Analyze. As a result, both the accounting information system and human resources had a positive effect on the quality of local government financial statements. Additionally, moderating variable with Moderated Regression Analysis showed that the external environment was able to moderate the human resources on the quality of local government financial statements. However, the environment could not moderate the accounting information system on the quality of local government financial statements.